A Primer on Exporting to Belize - Christina D. Storz; Timothy G. Taylor; Gary F. Fairchild (EDIS)
Every year the U.S. Department of State publishes extensive Country Commercial Guides for a large number of countries. These guides provide a great deal of information useful to individuals interested in developing exports markets either through direct exports or through direct foreign investment. This paper provides an abridged version of the Country Commercial Guide for Belize as well as supplemental information of direct relevance to agribusiness firms It is hoped that the information contained in this report provides a useful starting point for individuals interested in exploring export or investment opportunities in Belize. This is EDIS document FE503, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published February 2005.